Метаболические особенности субпопуляций дендритных клеток - Таланкина, Анна (Journal of the Belarusian State University. Ecology, 2023)
Metabolism is an important mechanism that ensures the vital activity of cells and is an integral function of all living organisms. Recent studies have uncovered unique aspects of metabolism in dendritic cells, professional antigen-presenting cells. It was previously believed that DCs were relatively passive in metabolism, however, recent studies demonstrate their complex metabolic activity, including energy metabolism and the synthesis of biochemical molecules. Metabolic processes in dendritic cells have a direct impact on their functional properties and interaction with other cells. They also influence immune function and antitumor response, as dendritic cells play an important role in antigen presentation and immune system activation.Today, considerable attention is paid to the role of dendritic cells in the context of oncological diseases, which represent a group of the most dangerous pathologies, among which malignant neoplasms stand out for their aggressiveness and ability to evade immune control. Features of dendritic cell metabolism in neoplasms include glycolysis activation, increased amino acid requirements, and altered metabolic pathways. The study of the metabolic features of DC provides an opportunity to develop strategies for metabolic manipulation to modulate the immune and antitumor response. In addition, new prospects are opening up for the development of innovative immunotherapeutic strategies aimed at improving the effectiveness of cancer treatment and improving patient survival. This is an important area of research that could lead to the development of new therapeutic approaches and personalized cancer treatment.This article reviews the latest research on the characteristics of the metabolism of various subpopulations of dendritic cells in the context of oncological diseases and discusses the impact of metabolic changes on immune responses and possible strategies for using this information in the development of new treatments for neoplasms.